KEDUDUKAN ADVOKAT DALAM PEMBAHARUAN PARADIGMA PENEGAKAN HUKUM INDONESIA - Aristo Evandy Barlian (KEADILAN PROGRESIF, 2021)
Advocate or attorney is a legal profession which has become the profession of legal experts. Apart from that, the existence of an advocate as a law enforcer has actually been regulated in Article 5 of Law 18 of 2003 concerning Advocates (Advocate Law). However, the existence of article 5 paragraph (1) has not provided an explanation regarding the concrete form of advocates as law enforcers, this makes the existence of advocates as law enforcers still lacking clarity, especially in their role as one of the components in the criminal justice system in Indonesia. Based on this research, there are four urgencies for an advocate's position in the criminal justice system, namely: (a) advocate as a legal service provider and legal aid provider, (b) advocate as a supervisor and guardian of judicial integrity, (c) an advocate as a counterweight to the dominance of the enforcer. law, (d) advocate as a defender of human dignity. With the existence of four urgencies, the position of an advocate as law enforcer. It is hoped that this writing will be able to emphasize and strengthen the role of advocates as one of the components in the criminal justice system in Indonesia and all components of the law, further changes need to be made to Advocate regulations, especially regarding the problem of the judicial mafia and a concrete explanation of the role of advocates as law enforcers in Indonesia.